Meminimasi Waste pada Distribution Center Area Non Food dengan Pendekatan Lean Warehousing di Perusahaan Retail PT XYZ - Widodo, Dannya Fatima Hasnuagi; Sumiati, Sumiati (Universitas Batanghari Jambi, 2024)
PT. XYZ is a minimarket retail company that sells various needs of the community. PT One of the DCs is located in the city of Batam, this DC still has some waste that occurs in its warehousing activities so research needs to be carried out to eliminate this waste. To eliminate problems, an approach was taken using lean warehousing with the tools used being Value Stream Mapping (VSM), Process Activity Mapping (PAM), Gemba shikumi, 5 whys, Lean matrix 2 in the activity mapping process (Process Activity Mapping/PAM) in a warehouse which identified 18 Non-Value Added activities and after processing it with Gemba Shikumi, 4 critical wastes were obtained, consisting of errors in handover evidence, re-inputting data, errors in picking goods, and looking for replacement goods due to incorrect picking. The 4 (four) wastes were given proposals for improving employee training, restructuring the issuing flow, making product labels, internal audits and receiving automation systems. These improvement recommendations are estimated to reduce warehousing process time by 6720 seconds or the equivalent of 1.87 hours. This figure is quite significant because it represents a time reduction of 19.83% from the previous total warehousing process time which reached 33,887 seconds or 9.42 hours.